Immunohistochemical evaluation of the effects of nebivolol on intimal hyperplasia following endothelial injury - Akar, Ilker; Rahman, Ali; Colak, M. Cengiz; Ustundag, Bilal; Ozercan, Ibrahim Hanifi; Uysal, Ayhan (Tubitak Scientific & Technological Research Council Turkey, 2011)
Aim: Intimal hyperplasia is a vascular remodeling process. It is a clinical problem that forms in the vascular wall as a result of smooth muscle cell migration, proliferation, and extracellular matrix accumulation. In this study we examined the immunohistochemical evaluation of the effects of nebivolol on intimal hyperplasia in damaged endothelial tissue. Materials and methods: The study was conducted using 21 rabbits equally divided into 3 groups: control, solvent, and nebivolol. The rabbits in the control group only underwent balloon injury of the abdominal aorta. The rabbits in the solvent group and nebivolol group underwent balloon injury and were treated with solvent and nebivolol intraperitoneally during the study. At the end of the study, the abdominal aortas were harvested. The intimal and medial areas were measured and the intima/media ratios were calculated. Tissue nitric oxide levels were determined and immunohistochemical findings were evaluated. Results: Statistically there were no differences between the control and solvent groups with respect to the intimal and medial areas, intima/media ratios, or the tissue nitric oxide (NO) levels. The neointimal thickening was significantly less in the nebivolol group than in the control and solvent groups (P < 0.001). Intima/media ratio was decreased in the nebivolol group (P < 0.001). Tissue nitric oxide levels were greater in the nebivolol group than in the control and solvent groups (P < 0.01). Immunohistochemical data in the nebivolol group were significantly lower as compared with the other groups (P < 0.05). Conclusion: Nebivolol may be a useful agent in early restenosis after vascular reconstructive procedures.
Endotel hasarı sonrası oluşan intimal hiperplazi uzerine nebivololun etkilerinin immunohistokimyasal de?erlendirilmesi
Keywords: Intimal hyperplasia; nitric oxide; nebivolol